Relationship between Physical Activity and Triceps Skin Fold Thickness in adolescent girl students - Masoumeh Moghadam; ES Hajikazemi; Farah RoozberM; Anahita Hoshyar rad; Agha Fatemeh Hosseini (Iran University of Medical Sciences, 2011)
Background and Aims: In recent decades reduction in physical activity had become as one of important factors in increasing obesity in all people especially in adolescents. The aim of this study was to determine relationship between physical activity and triceps skin Fold Thickness in adolescent girls.   Material and Method: It was an anticipational correlational study. Three hundred eighty five girls in high school were selected randomly. They neither had known physical/mental diseases, nor were engaged in sport teams. They also had not special diets. Data collection was done by IPAQ (short form) and caliper. Analysis was done by ANOVA, Chi square, and Spearman correlation using SPSS - PC (14version).   Results: Data indicated that almost half of student had low physical activity and according to triceps skin fold thickness they were included in over weight and obess group. However, no significant correlation was seen between physical activity and skin fold thickness.   Conclusion: Although there was no correlation between Physical activity and obesity, but systematic programs to enhance adolescent's activity and to promote their health could be commended.